Linguistic Features’ Variation in Translating Technical Texts - Al-Awabdeh, Abdul- Hamed (Journal of Social Sciences (COES&RJ-JSS), 2020)
This research examines the contribution of language variation in translating technical texts from English into Arabic language. It aims at analyzing language variation, technical texts translation competence, creating subject field knowledge and generating authenticity in technical texts and translation setting. This study attempts to uncover problems that English language and literature students at the University of Jordan / Aqaba branch problems of translating technical texts. This qualitative research included 30 B.A students selected randomly from the Dept. of English Language and Literature at the University of Jordan. The results of the study revealed that literature students encountered many problems when translating technical texts, particularly when using two different varieties of English American / British into Arabic language. This research recommends that translators and professional in the field should be concerned with translating technical texts and include them in translation syllabi.